Pattern of Drugs Use in Selected Paediatric Diseases in Outpatients Departments of Public and Private Teaching Hospitals in Bangladesh - Afrin, Tasnin; Afroz, Rumana; Sultana, Shahin; Kamrunnesa, -; Lotus, Mahbuba Jahan; Ara, Ferdous (Ibrahim Cardiac Medical Journal, 2020)
Background & objective: Appropriate use of drugs are important in any diseases in any population. It is particularly so in children. To evaluate whether drugs are properly utilized in terms of efficacy, safety, convenience and economic aspects at all levels in the chain of drug use, periodic studies addressing the utilization of drugs in different health care setting are essential. Various drug utilization studies have been carried out all over the world but there are limited studies addressing drug use patterns in pediatric population in Bangladesh. The present study is one such step to evaluate the pattern of drug use in different pediatric diseases among patients attending at pediatric out-patient department (OPD) in two selected medical college hospitals. Methods: This cross-sectional study was conducted in the paediatric OPD of two tertiary care hospitals, Sir Salimullah Medical College & Mitford Hospital (SSMC & MH) (a public hospital), Dhaka and Dhaka National Medical College (DNMC) & Hospital (a private hospital). A total of 600 children (300 from each of the two Medical College Hospitals) were selected as study subjects. Three hundred prescriptions audited in SSMC & MH contained a total 946 drugs and 300 prescriptions audited in DNMC contained 990 drugs in total. Patients got admitted during out-patient department visit were excluded from the study. The age and sex of the patients and medications use-related variables like dose, frequency, duration and route of administration of the drugs were noted. Pattern of drug use in the hospitals for pediatric population was evaluated. Results: The study subjects of the two tertiary hospitals were almost identical in terms of age and sex (p = 0.181 and p = 0.369 respectively). Use of three drugs per encounter was commonly observed in both the hospitals. Around one-third of the prescriptions contained four drugs. Prescription of five drugs was rare in both the hospitals. Prescription with two drugs was higher in SSMC & MH than that in DNMC Hospital (p = 0.043). Majority of the prescriptions from SSMC (83.1%) contained drugs within essential drug list (EDL) compared to that from DNMC (73%) (p< 0.001). The highest prescribing drug was antibiotic, both in SSMC (22.7%) and DNMC (23.2%) (p = 0.417) followed by analgesic (18% in SSMC and 17.7% in DNMC), anti-diarrhoeal. The less commonly used drugs were gastric acid suppressant, antispasmodic, anthelmintic, antiemetic, while rarely prescribed drugs were antihistamines, antiasthmatic and nasal drops. Pattern of drugs prescribed in two hospitals were similar (p > 0.05). Conclusion: The study concluded that the rate of antibiotics prescribed in both public and private hospitals is higher. Further studies teaching hospitals etc. are required for the monitoring of drug utilization pattern and formulation of Standard Treatment Guidelines (STG) for the physicians is essential. Ibrahim Card Med J 2019; 9 (1&2): 54-59